99mTc-Pyridoxylidene Glutamate —A Radiopharmaceutical for the Hepatobiliary System - Noronha, O. P. D.; Sewatkar, A. B.; Ganatra, R. D.; Subramanian, G. (Nuklearmedizin - NuclearMedicine, 1976)
99mTc-pyridoxylidene glutamate is a good agent to visualize the hepatobiliary system. The method of preparation and quality control, and preliminary data on its behaviour in human controls is presented. In humans the gall bladder could be well seen in about 15—20 minutes after intravenous injection.